“NotalastÍrÍw hám kompyuter dástÚrlerinde islew” pániN oqÍtÍwda Sibelius nota redaktorÍnan paydalanÍw metodikasÍ - Abılova, G. (SCIENCE and SOCIETY, 2021)
The article discusses the use of computer technology in teaching musical subjects. Methodology of using the Sibelius music editor. There is given main features of the program, methods of application, program interface, editing scores. This article enables students and music teachers to effectively use the unlimited possibilities of music editors in the process of musical activity.
Keywords: note; program; score; keyboard; music; instrument panel